Pengaruh Overconfidence Bias, Herding Bias, Representativeness Bias, Loss Aversion dan Risk perception terhadap Investment Decision di Kota Batam - Johny Budiman; Patricia Patricia (Universitas Internasional Batam, 2021)
This research aimed to analyze the impact of overconfidence bias, herding bias, representativeness bias, loss aversion, and risk perception toward decision making in Batam. The object of this research is the investors in Batam. Primary data are collected using questionnaires answered by 203 respondents. The analysis method that was used is Partial Least Squares by using SmartPLS version 3.2. This research showed that overconfidence bias, herding bias, representativeness bias have a significantly positive impact on investment decision, whereas loss aversion and risk perception do not have a significant impact on investment decision.